Genotoxicity analysis by presence of arsenic in soil: test tradescantia micronucleus extracts by clone 4430 (trad-mcn) - Rico Rodríguez, Miguel Angel; prieto García, Francisco; Otazo Sánchez, Elena María; Prieto Méndez, Judith; Acevedo Sandoval, Otilio Arturo (Biotecnología en el Sector Agropecuario y Agroindustrial, 2019)
Arsenic is a toxic metalloid that is present in air, water and soil. Soil bacteria play an important role in the oxidation of this element. This article describes the use of plants as bioassay for the detection of genotoxicity induced leaching of soils with arsenic (As). Test micronuclei induction was used stem cells pollen Tradescantia clone 4430 (Trad-MCN). The results demonstrate that the micronuclei frequency was higher for soil leachate from the community of the Salitre, Hidalgo, and the community of Bella Vista del Río, Queretaro, in Mexico. Compared with the control group of leachates soil for the Municipality of Querétaro. In all cases there was a significant difference (Tukey p> 0,05). Also resulting in good linear correspondence R2 = 0,94 and the slope of the equation that represents a velocity induced MNs 100/0,05 tetrads each μgAs.L-1.